The state‐of‐the‐art in digital technology‐based assessment. (30th March 2018) - O'Leary, Michael; Scully, Darina; Karakolidis, Anastasios; Pitsia, Vasiliki
Abstract: The role of digital technology in assessment has received a great deal of attention in recent years. Naturally, technology offers many practical benefits, such as increased efficiency with regard to the design, implementation and scoring of existing assessments. More importantly, it also has the potential to have profound, transformative effects on the field of assessment by facilitating the integration of formative activities with accountability requirements and broadening the range of abilities and the scope of constructs that can be assessed. This article provides an overview of the current state‐of‐the‐art in digital technology‐based assessment, with particular reference to advances in the automated scoring of constructed responses, the assessment of complex 21 st century skills in large‐scale assessments and innovations involving high fidelity virtual reality simulations. Key challenges with respect to each are highlighted before the extent to which digital technology is truly transforming assessment is considered.